2012
DOI: 10.1093/jxb/ers328
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genetic analysis ofArabidopsis thalianaanthocyanin biosynthesis mutants under chronic adverse environmental conditions

Abstract: Anthocyanin production is a characteristic response of flowering plants to unfavourable environmental conditions. The potential roles of flavonoids and anthocyanins in plant growth were investigated by growing Arabidopsis thaliana anthocyanin production mutants (transparent testa) under limiting nitrogen and high light conditions. Inability to produce kaempferol or subsequent intermediate compounds by some transparent testa lines was correlated with less biomass accumulation in mature plants compared with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 57 publications
1
55
0
Order By: Relevance
“…In previous work, the dry weight and stem height measurements of an Arabidopsis chs mutant did not differ from those of control plants Vanholme et al, 2010b). In a different study using the same chs mutant, reduced growth was observed versus control plants when grown under adverse environmental growth conditions, such as high light intensity and nitrogen starvation (Misyura et al, 2013), indicating that the growth phenotype is dependent on the environment. C2-Idf maize plants might allocate more carbon to biomass production by saving on plant defense compounds (among which flavonoids are made via CHS).…”
Section: Discussionmentioning
confidence: 80%
“…In previous work, the dry weight and stem height measurements of an Arabidopsis chs mutant did not differ from those of control plants Vanholme et al, 2010b). In a different study using the same chs mutant, reduced growth was observed versus control plants when grown under adverse environmental growth conditions, such as high light intensity and nitrogen starvation (Misyura et al, 2013), indicating that the growth phenotype is dependent on the environment. C2-Idf maize plants might allocate more carbon to biomass production by saving on plant defense compounds (among which flavonoids are made via CHS).…”
Section: Discussionmentioning
confidence: 80%
“…However, wide ranges of primary and secondary metabolites are involved in the stress tolerance (Arbona et al, 2013;Ramalingam et al, 2015;Rodziewicz et al, 2014). Under different treatments, anthocyanin accumulation is considered as a positive response to oxidative stress (Diaz et al, 2006;Hughes et al, 2010;Misyura et al, 2012). In addition, the accumulation of carotenoids is regarded to suppress the oxidation (Cao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify such mutations and establish their exact effects on the flavonoid pathway and on flavonoid profiles. Such studies have been carried out in other plants like arabidopsis, alfalfa and barley (Misyura et al, 2012;Abrahams et al, 2002;Bowerman et al, 2012;Buer and Djordjevic, 2009;von Wettstein 2007). However, similar studies are yet to be carried out in sorghum, hence this study is aimed at attempting to establish a link between sequence polymorphisms at the ANS gene locus and differences in proanthocyanidin profiles in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest is to find out if any sequence polymorphisms at this locus may explain observed differences in grain proanthocyanidin profiles. A number of flavonoid ANS gene mutants in Arabidopsis, namely tt 11, tt17 and tt 18 (tds-4) have been identified and characterised in Arabidopsis and alfalfa, both at the biochemical and molecular level (Misyura et al, 2012;Bowerman et al, 2012;Abrahams et al, 2002;Buer and Djordjevic, 2009). All these mutants were characterised by altered flavonoid profiles and deposition patterns in the grain.…”
Section: Introductionmentioning
confidence: 99%